Assessment of biological safety of fermented phyllanthus emblica fruit juice - Chaiyavat Chaiyasut (2018)
© 2018 The Authors. Objective: The present study evaluated the subchronic toxicity of Lactobacillus mediated fermented Phyllanthus emblica fruit juice (FPJ) using a rat as a model system. Methods: FPJ was prepared, and estimated the changes in pH by pH meter, and microbial load by a plating method. Rats were fed with different dose of FPJ for 60 days. The changes in the body mass were noted. The blood and organs of the experimental rats were collected, after 60 days of intervention. Then, they were analyzed for the selected hematological and biochemical parameters by following standard hospital protocols. Results: The pH of FPJ after 30 days of fermentation was 3.16. FPJ was rich in probiotic Lactobacillus spp. (7.23 Log CFU per mL) without contamination. The supplementation of FPJ was not significantly affected the body weight of the experimental animals, except the female rats in posteffective dose (PED) group showed significant changes (20.83±8.49 g) compared to control (40±17.22 g). The internal organs of the rat were not affected by the FPJ supplementation. The changes observed in blood urea nitrogen, creatinine, cholesterol, triglyceride, aspartate aminotransferase; alanine aminotransferase, and alkaline phosphatase level of experimental rats, both male and female, were not significantly differed from the respective controls. The average of lymphocytes level was significantly increased in continuous dosing group of males and females. Interestingly, the increase in red blood cell and hemoglobin (HGB) were statistically significant for ED group and PED in both sexes, except for females with no effect on HGB content. Conclusion: The prepared FPJ was enriched with probiotic Lactobacillus spp. The supplementation of FPJ (up to 9 mL/kg/day) for 60 days was not significantly influenced the body weight, internal organs, biochemical and hematological parameters of experimental rats (both male and female). The results revealed that FHJ is suitable for the human consumption.